The Evolution of Minangkabau Elite: Modernization and Cultural Shifts in Nagari Kurai, 19th-20th Century - Andoni, Yudhi (Faculty of Humanities, Andalas University, Padang, West Sumatra in cooperation with Kato Institute., 2024)
The problem addressed in this research focuses on the socio-cultural transformation of the Minangkabau elite during the colonial period, particularly in Nagari Kurai. Using the historical research method, the study traces the evolution of the local elites through archival analysis and ethnographic records. The key finding reveals that the establishment of Bukittinggi as a colonial center and the spread of modernity in the early 20th century prompted the rise of a new urban elite, distinct from traditional authorities. In conclusion, the study suggests that colonial modernity played a pivotal role in reshaping cultural and political hierarchies in Minangkabau society.